The effect of drinking cold water on nausea and vomiting among patient with post-chemotherapy breast cancer - Wella Juartika (The Journal of Palembang Nursing Studies, 2022)
Background: Nausea, vomiting after chemotherapy is still major problem that interferes with the process of treating cancer, especially breast cancer. There are 2 things that can be done to reduce nausea, vomiting, pharmacologically and non-pharmacologically. Drinking cold water is one of the non-pharmacological ways for patients who experience nausea, vomiting after chemotherapy. These actions can reduce acute nausea and vomiting delayed due to chemotherapy Purpose: The purpose of this study was to determine the effect of drinking cold water on nausea and vomiting after chemotherapy in breast cancer patients in RSUP M. Djamil Padang. Methods: This research was a time series. Sampling by consecutive sampling and determination of intervention and control groups by randomization of simple subject allocations. The research sample consisted of 38 respondents, consisting of 19 respondents as an intervention group who were treated with cold drinking water for 3 days and 19 respondents as a control group Results: Testing the difference in the decrease in the average score of nausea and vomiting in the intervention group using the repeated measure ANOVA test. The results showed an average decrease in the intervention group of < 0.001. Conclusions: The conclusion significantly drinking cold water can reduce nausea and vomiting after chemotherapy in breast cancer patients in RSUP M. Djamil Padang. It is recommended that drinking cold water be applied as part of nursing intervention in providing nursing care to patients who experience nausea and vomiting after chemotherapy.